2021
DOI: 10.31202/ecjse.868373
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of marble quarries expansion and land cover changes using satellite images and GIS on a rural settlement of Burdur province, Turkey

Abstract: This study was actualized in Karamanlı district of Burdur province in order to draw attention to the increase in the surface areas of marble quarries and to monitor the changes of land cover types during the period from 1995 to 2020. Geographic information system tools and supervised maximum likelihood classification approach provided a methodological basis for this study. Landsat satellite images used in this study were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Tercan and Dereli (2021) found that forest and semi-natural areas are generally allocated to marble quarries and the quarries, which is 4.69% of total area, showed a serious increase of 891.44% (average 164.48% in five years) between 1995 and 2020 in Burdur province. According to our calculations using growing rate of Tercan and Dereli (2021) ( R = 0.98 p < 0.01 between percentage of MQA in total area and year), it is expected that even if no new marble quarry is established as of today, because the marble quarries have been established throughout the Taurus Mountains, 7.14 % of the Taurus in 2027 and ten years later, in 2032, the 8.25 % of the Taurus habitats may have disappeared. This situation will lead to both the extinction of locally endemic species and the extinction of the genetic structures of many species specific to the Taurus Mountains.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tercan and Dereli (2021) found that forest and semi-natural areas are generally allocated to marble quarries and the quarries, which is 4.69% of total area, showed a serious increase of 891.44% (average 164.48% in five years) between 1995 and 2020 in Burdur province. According to our calculations using growing rate of Tercan and Dereli (2021) ( R = 0.98 p < 0.01 between percentage of MQA in total area and year), it is expected that even if no new marble quarry is established as of today, because the marble quarries have been established throughout the Taurus Mountains, 7.14 % of the Taurus in 2027 and ten years later, in 2032, the 8.25 % of the Taurus habitats may have disappeared. This situation will lead to both the extinction of locally endemic species and the extinction of the genetic structures of many species specific to the Taurus Mountains.…”
Section: Discussionmentioning
confidence: 98%
“…It is not precisely known whether the number of marble quarries in Turkey has increased in the last decade, but exports amounted to $ 4.6 million in 2000 (about 500 quarries) and increased 370-fold to $ 1.7 billion in 2020 (about 1500 quarries) (Ticaret Bakanlığı 2021). Marbele quarries showed a very serious increase of 891.44% (from 148.41 hectares to 1577.52 hectares) between 1995 and 2020 in a local area of Taurus Mountain (Tercan and Dereli 2021). Marble quarries are operated with low productivity due to the rock structure of the Taurus.…”
Section: Introductionmentioning
confidence: 99%
“…Tercan and Dereli [28] found that forest and semi-natural areas are generally allocated to marble quarries, which take up 4.69% of the total area and showed a serious increase of 891.44% (average 164.48% in five years) between 1995 and 2020 in Burdur province. According to our calculations using the growth rates of Tercan and Dereli [28] (R n = 0.98 p < 0.01 between percentage of MQA based on total area and year), it is expected that even if no new marble quarries are established as of today, because the marble quarries have been established throughout the Taurus Mountains, 7.14% of Taurus habitats in 2027 (and 8.25% by 2032) may have disappeared. This situation will lead to both the extinction of locally endemic species and the extinction of the genetic structures of many species specific to the Taurus Mountains.…”
Section: Potential Impact Of Marble Quarries On the Wider Taurus The ...mentioning
confidence: 99%
“…It is not precisely known whether the number of marble quarries in Turkey has increased in the last decade, but exports amounted to USD 4.6 million in 2000 (about 500 quarries) and increased 370-fold to USD 1.7 billion in 2020 (about 1500 quarries) [27]. Marble quarries showed a very serious increase of 891.44% (from 148.41 hectares to 1577.52 hectares) between 1995 and 2020 in a local area of the Taurus Mountains [28]. These marble quarries operate with low productivity due to the rock structure of the Taurus Mountains.…”
Section: Introductionmentioning
confidence: 99%